Better Board Education for Better Leadership and Management in the Health Sectors of Low and Middle Income Countries - Sikipa, Godfrey; Osifo-Dawodu, Egbe; Kokwaro, Gilbert; Rice, James A. (Frontiers in Public Health, 2019)
Board member education must be elevated within the curricula of leadership development programming in Low and Middle Income Countries (LMICs) across the globe. This article reviews trends and patterns in how educators of health system leaders in low resourced countries are exploring ways to unleash the value of good health sector boards of directors or trustees. When properly developed and supported, the community, business, and health sector leaders serving on these boards can create the conditions within which those who deliver and manage health services are more likely to successfully achieve the mission of their organizations